2012
DOI: 10.2320/matertrans.mb201201
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Bonding Behavior between Silver Nanoparticles and Gold Substrate Using Molecular Dynamics Simulation

Abstract: Molecular dynamics (MD) simulation was applied to the sintering behavior of silver nanoparticles on a gold substrate in order to elucidate the sintering mechanism of the nanoparticles on the substrate. The simulation revealed that silver atoms from 1 and 2 nm nanoparticles migrated freely because of their larger surface energy and then epitaxially reoriented to the gold substrate so as to reduce grain boundary energy. The silver nanoparticles were more spread out on the (011) gold substrate than on the (001) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In this bonding process, sintering can occur at a temperature lower than 300 C only when Ag exists in the form of nanoparticles, as their signi cantly high surface energy results in necking and subsequent agglomeration, causing relaxation and the minimization of their energy 5,8,10) . It can be concluded that quick ring is advantageous in that it allows one to bypass the low-temperature regime, resulting in an increase in the surface energy at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this bonding process, sintering can occur at a temperature lower than 300 C only when Ag exists in the form of nanoparticles, as their signi cantly high surface energy results in necking and subsequent agglomeration, causing relaxation and the minimization of their energy 5,8,10) . It can be concluded that quick ring is advantageous in that it allows one to bypass the low-temperature regime, resulting in an increase in the surface energy at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Various materials have been proposed for replacing these high-melting-point solders. Studies exploring the use of nanoparticles as a bonding material have shown that they have great potential in terms of the joint shear strength [1][2][3][4][5][6] . Furthermore, we have successfully used Ag 2 O as a bonding material, replacing the nanoparticles as the original material and thus lling the cost gap between conventional solders and nanoparticle-based materials [7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the crystal orientation of the sintered silver corresponds to that of the gold substrate in the vicinity of the bonding interface. 21,22) However, further reduction in the bonding temperature is required to reduce the residual thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…The atoms and molecules are allowed to interact for a period of time, giving a view of the motion of the atoms. Xu et al, 3) Kart et al, 4) Ogura et al 5) used Molecular Dynamics to study the sintering behavior of nanoparticles.…”
Section: )mentioning
confidence: 99%